Impact of incorporating inorganic additives in processed meat production - Dissanayake, Kasun; Rifky, Mohamed; Farmonov, Jasur; Boynazarova, Yulduz; Meyliyev, Akhror; Zokirov, Kurbonalijon; Narziyev, Farrux; Samadiy, Murodjon (E3S web of conferences, 2024)
This study explores the complex effects of inorganic chemicals on the quality of meat and the health of consumers at different stages of processing. It is determined that nitrites, phosphates, potassium sorbate, sodium chloride, antioxidants, and monosodium glutamate (MSG) contribute to improving meat products’ sensory qualities, shelf life, and oxidative stability. On the other hand, health problems related to their consumption, including metabolic disorders and carcinogenicity, are a cause for concern. The clean-label effort has impacted consumer opinions, which in turn have created demand for natural and additive-free meat. As inorganic compounds are essential to the processing of meat, initiatives are being made to develop solutions that will satisfy customer preferences. The study underlines the need for more research into the complex relationships between chemicals and meat quality, enabling the manufacture of meat products that are healthy, secure, and attractive in accordance with changing customer preferences and health considerations.